PENGARUH KUALITAS PELAYANAN, KEPUASAN PELANGGAN, CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN PADA PT. SUAR NUSA JAYA TOUR - Ni Kadek Intan Nia Putri; A. A. Putu Agung; Ni Putu Nita Anggraini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Customer loyalty is a deep enduring customer commitment to re-subscribe or consistently repurchase selected products or services in the future, even though the influence of the situation and marketing efforts have the potential to cause behavior change. This study aims to test and obtain empirical evidence of the effect of service quality, customer satisfaction, company image on customer loyalty at PT. Suar Nusa Jaya Tour. The population in this study were all consumers of PT. Suar Nusa Jaya Tour which does not know the number and determination of the sample using the Ferdinand formula so that 45 people are used as samples. Sampling using purposive sampling method. The analytical tool used to test the hypothesis is multiple linear regression analysis. The results showed that customer satisfaction has a positive and significant effect on customer loyalty at PT. Suar Nusa Jaya Tour. Further research is expected to develop this research with other variables which theoretically have an influence on customer loyalty.